TOURISM DEVELOPMENT STRATEGY IN SKIKDA: BETWEEN RHETORIC AND PRACTICE - Ahmed Soufiane SID (International Journal of Innovative Technologies in Social Science, 2023)
Presently, tourism is recognized as a crucial driver for generating added value and a viable option for global economic revitalization and development, particularly in developing nations. Our selection of this topic emerged from an examination of the tourism sector in Algeria, with a specific focus on the Skikda Department. This examination revealed certain deficiencies associated with this destination. Consequently, we contend that the tourism sector in Algeria confronts a myriad of challenges and threats, resulting in a continual decline in its share of the global tourism market in recent times.